2018
DOI: 10.3390/rs10070986
|View full text |Cite
|
Sign up to set email alerts
|

Glacier Change, Supraglacial Debris Expansion and Glacial Lake Evolution in the Gyirong River Basin, Central Himalayas, between 1988 and 2015

Abstract: Himalayan glacier changes in the context of global climate change have attracted worldwide attention due to their profound cryo-hydrological ramifications. However, an integrated understanding of the debris-free and debris-covered glacier evolution and its interaction with glacial lake is still lacking. Using one case study in the Gyirong River Basin located in the central Himalayas, this paper applied archival Landsat imagery and an automated mapping method to understand how glaciers and glacial lakes interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 78 publications
1
31
0
Order By: Relevance
“…Numerous authors have found similar model results in the Himalaya (e.g. Scherler et al, 2011;Rowan et al, 2015;Jiang et al, 2018). We have presented supra-glacial debris cover change over the last 30 years in the Greater Caucasus region.…”
Section: Possible Reasons For Supra-glacial Debris Cover Changessupporting
confidence: 75%
See 2 more Smart Citations
“…Numerous authors have found similar model results in the Himalaya (e.g. Scherler et al, 2011;Rowan et al, 2015;Jiang et al, 2018). We have presented supra-glacial debris cover change over the last 30 years in the Greater Caucasus region.…”
Section: Possible Reasons For Supra-glacial Debris Cover Changessupporting
confidence: 75%
“…Supra-glacial debris cover affects surface melt with increasing ablation in cases of thin debris cover (less than a few cm) or decreasing ablation under continuous thick debris cover (Östrem, 1959;Nicholson et al, 2018). Obtaining information about debris cover is relevant not only with respect to its impact on glacier ablation but also because it is an important part of the sediment transport system (supra-glacial, englacial and subglacial) in cold and high mountains (Kellerer-Pirklbauer, 2008), which ultimately affect the overall dynamics and mass balance of the glaciers. Several studies show an increase in debris-covered area with overall glacier shrinkage and mass loss (Deline, 2005;Stokes et al, 2007;Kirkbride and Deline;Glasser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This step was necessary for the removal of misclassified polygons of glacial lakes due to shadow and also to ensure precise lake delineations. Lakes above 2450 m that were not glacial lakes were discarded by checking the nearest glacier and Google Earth visual interpretation; meanwhile, very few glacial lakes (n = 32) were found in the elevation zone of 2450-4000 m. In addition, quality assurance and quality control (QA/QC) procedures were conducted following the procedures mentioned in the previous studies [9,33]. The obtained lakes were cross-checked with previous data [1,20], historical images in Google Earth, and a base map of World Imagery (Esri, DigitalGlobe, GeoEye) to remove misclassified lakes and add a few missed lakes by manual digitization.…”
Section: Methodsmentioning
confidence: 99%
“…The Gandaki River basin has many run-of-river (ROR) glacier-fed hydropower plants under operation and construction that lie on potential GLOF pathways of high risk lakes [23,31]. In the adjacent areas of the Nepal Himalaya (in particular, Tibet, China), considerable lake formations have been reported on the Tibetan glaciers that feed into Nepalese rivers [32,33]. These glacial lakes deserve the utmost attention, as their failure poses a regional threat.…”
Section: Introductionmentioning
confidence: 99%